Sudden death as a first manifestation of left atrium thrombus in rheumatic severe mitral stenosis. Issue 3 (September 2019) - Ahmed, Mawada; Fadel, Bahaa; Alamri, Mohammed; Galzerano, Domenico; Alassas, Khadija; Vriz, Olga
Abstract: Left atrium and left atrial appendage thrombus is common in patients with mitral stenosis, causing significant morbidity and mortality. We described a case of rheumatic mitral stenosis, a 48-year-old female patient, who had undergone percutaneous transvenous mitral commissurotomy 26 years back. She presented with an episode of palpitations and breathlessness on mild exertion. She found to have rapid atrial fibrillation and heart failure. Her echocardiography showed severe mitral stenosis and large left atrial thrombus intermittently obstructing the mitral valve. While she was prepared for urgent valve replacement she had cardiac arrest and died. The echocardiogram showed the thrombus was stuck and closed the mitral valve orifice. From this events we did a review in our institution about the mitral stenosis patients who found to have left atrium thrombus by routine transthoracic echocardiography in five years period. Looking for factors contributing to thrombus formation and outcome predictor, as to outline management plan. <Learning objective: Our aim is to give more attention to the factors contributing for left atrium thrombus formation and thrombus character in mitral stenosis patients and its clinical impact to prevent miserable events in such high risk patients.>